(untitled) (Tạp chí Y học Cộng đồng, 2025)
Introduction: Population aging is a significant challenge for Vietnam, particularly in urban areas, where the proportion of elderly individuals is increasing. Describing health-related quality of life (HRQoL) and associated factors in the context of this aging process plays a crucial role in shaping future elderly care services and policies. The aim of this study is to measure HRQoL and identify related factors among elderly individuals (aged ≥60) living in urban areas of Vietnam. Methods: This cross-sectional study was conducted in Ward 16, District 8, one of the most populous wards in Ho Chi Minh City. HRQoL was measured using the EuroQol-5 dimensions-5 levels (EQ-5D-5L) instrument. A convenience sampling technique was employed with a sample frame of 2,447 elderly individuals. A total of 387 elderly individuals were selected from this sample frame between March and April 2021. Inclusion criteria: individuals aged ≥60 years living in Ward 16 at the time of the study and who agreed to participate. Exclusion criteria: elderly individuals with mental health issues, those unable to answer independently, or those with missing information for any of the five domains (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression). Results: The EQ-5D-5L index of older people had a median of 0.931 (IQR 0.847-1.000); the EQ VAS score had a median of 70 (IQR 60-80). The mean EQ-5D-5L index was 0.884 (SD = 0.18); the mean EQ VAS score was 72.14 (SD = 15.51). The study found a correlation between age group, sex, education, income-generating work, self-rated economic status, and most health issues with HRQoL. Conclusion: The results of this study serve as a reference for public health programs supporting the elderly population, particularly in urban areas. Furthermore, elderly individuals will have a clearer understanding of their HRQoL and be able to implement appropriate personal solutions to improve their HRQoL.